Analisis Pengaruh Tingkat Kriminalitas dan Kepadatan Penduduk Terhadap Indikator Kualitas Hidup Masyarakat melalui Pendekatan Two-Way MANOVA - Dewi, Ni Luh Ayu Nariswari; Zalfa Assyadida, Azizah; Salma Namira, Alivia; Nasrudin, Muhammad; Trimono, Trimono (EKSPONENSIAL, 2025)
Quality of a population life is shaped by various social and structural conditions, including socioeconomic disparities, crime levels, and population pressure. Understanding how these factors interact is essential for evaluating regional welfare. Therefore, this study aims to examine the influence of crime rates and population density on the quality of life in Indonesia using a Two-Way Multivariate Analysis of Variance (MANOVA) approach. The dependent variables analyzed include the Human Development Index (IPM), the percentage of the poor population, and the open unemployment rate. The independent variables consist of categories of crime rates and population density levels. Prior to conducting the MANOVA, assumption tests were performed to ensure data adequacy, including multivariate normality testing using Mardia’s test, independence testing via Bartlett's Test of Sphericity, and homogeneity of variance testing with Box’s M Test. The analysis results indicate that neither crime rates nor population density levels significantly influence the three quality of life indicators simultaneously, as evidenced by the Wilks’ Lambda and Pillai’s Trace test outcomes. These findings suggest that policies aimed at improving quality of life should not solely focus on crime rates and population density but require a multidimensional approach encompassing other factors such as education, healthcare, and economic conditions.